Numerical Study on Two-Dimensional Micro-Channel Flows Using the Gas-Kinetic Unified Algorithm (Communications in Computational Physics, 2018)
Based on the Boltzmann model equation, the Gas-Kinetic Unified Algorithm(GKUA) will be developed to simulate the two-dimensional micro-scale gas flows withirregular configuration. The numerical scheme for the direct evaluation of the unifiedvelocity distribution function in the computable model of the Boltzmann equationand the multi-block grid docking technology are constructed, and the numericalprocedures of characteristic-based boundary conditions are presented to modelthe gas-surface interaction and the inlet/outlet boundaries for the two-dimensionalmicro-channel flows. The two-dimensional Couette flow, the pressure-driven micro-channelflows, and the irregular micro-orifice flows in different scales are numericallysolved from high rarefied free-molecule to near-continuum flow with the Knudsennumbers of $Kn$ = 100−0.01. The computed results are compared and validated withthe DSMC data in the transitional flow regime and the slip N-S solutions in the near-continuumflow regime, in which the GKUA is verified accurately and smoothly tosimulate the two-dimensional micro-channel flows with strong adaptability and goodprecision. The micro-channel flow features with the wide range of $Kn$ numbers in thenear-continuum slip and transitional flow regimes are revealed, and it is probable toprovide a way in developing a new numerical algorithm for micro-scale flows.